2014
DOI: 10.1111/ejn.12647
|View full text |Cite
|
Sign up to set email alerts
|

Effect of amiloride on endoplasmic reticulum stress response in the injured spinal cord of rats

Abstract: After traumatic spinal cord injury (SCI), endoplasmic reticulum (ER) stress exacerbates secondary injury, leading to expansion of demyelination and reduced remyelination due to oligodendrocyte precursor cell (OPC) apoptosis. Although recent studies have revealed that amiloride controls ER stress and leads to improvement in several neurological disorders including SCI, its mechanism is not completely understood. Here, we used a rat SCI model to assess the effects of amiloride on functional recovery, secondary d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Studies have also demonstrated that the administration of amiloride, which enhances the ER stress response, decreased OPC apoptosis [ 11 , 12 ]. In our previous study by Kuroiwa, et al [ 9 ], we demonstrated that amiloride administration increased GRP78 expression and decreased CHOP expression within the spinal cord, which decreased neural cell apoptosis and led to an increase of OPCs in the injured spinal cord. The group treated with amiloride had improved motor function compared to the control group up to 28 days after injury.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…Studies have also demonstrated that the administration of amiloride, which enhances the ER stress response, decreased OPC apoptosis [ 11 , 12 ]. In our previous study by Kuroiwa, et al [ 9 ], we demonstrated that amiloride administration increased GRP78 expression and decreased CHOP expression within the spinal cord, which decreased neural cell apoptosis and led to an increase of OPCs in the injured spinal cord. The group treated with amiloride had improved motor function compared to the control group up to 28 days after injury.…”
Section: Introductionmentioning
confidence: 58%
“…Compared to control animals, the rats that received amiloride administration had enhanced ER stress responses, with significantly increased expression of GRP78 and decreased expression of CHOP. The enhanced ER stress response led to a significant reduction in apoptosis and secondary injury expansion, and induced a significant increase in OPCs [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, spinal cord injury (SCI) induced by addictive drugs attracts less attention. It has been reported that opioid addiction affects myelination ( 4 ). It is still unknown whether METH induces demyelination in spinal cord.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress ( 5 ), inflammation ( 6 ), endoplasmic reticulum (ER) stress ( 7 ), ecotoxicity, and dysregulation of metabolic processes are involved in SCI. After traumatic SCI, ER stress exacerbates secondary injury, leads to expansion of demyelination and reduction of remyelination resulting from oligodendrocyte precursor cell apoptosis ( 4 ).…”
Section: Introductionmentioning
confidence: 99%